Aktivitas Antioksidan dan Tabir Surya Ekstrak Etanol Tanaman Crassocephalum crepidioides (Benth.): Antioxidant and Sunscreen Activity of Ethanol Extract of Crassocephalum crepidioides (Benth.) - Rolan Rusli; Ismah Nuri; Mahdyya Afiana Ramadani; Vita Olivia Siregar; Mukti Priastomo; Muhammad Faisal (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Crassocephalum crepidioides (sintrong) plant has secondary metabolites such as flavonoids, saponins, steroids, and tannins which are thought to have antioxidant and sunscreen activities. Antioxidant activity of the ethanol extract of the leaves and flowers of Sintrong was measured using Uv-Vis spectrophotometry obtained IC50 values of 23.558 ppm (flowers) and 0.62 ppm (leaves), and categories as very strong antioxidants. Based on %Te and %Tp values, ethanol extract of sintrong leaves was categories as sunblock, while ethanol extract of flowers of sintrong was categories as Fast Tanning (for %Te) and for %Tp was categories as suntan standard (for 200-300 ppm) and Extra Protection (for 400-600 ppm). The SPF of the ethanol extract of the leaves and flowers of sintrong is categories as minimal protection.